500 kV SF₆-Insulated Circuit Breaker Maintenance Simulator - Domingues, Gustavo C.; Oliveira, Leticia Z. de; Jesus, Thaynara N. de; Macedo, Jose Lucas H.; Peres, Fabiana F. F.; Mauricio, Claudio R. M.; Peretti, Adriano; Lee, Alan de Oliveira (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais Estendidos do XXVII Simpósio de Realidade Virtual e AumentadaDO - 10.5753/svr_estendido.2025.15770, 2025)
The maintenance of 500 kV circuit breakers with SF6 insulation is a highly complex procedure for which conventional training methods present high risks and costs. This work presents the development of a VR simulator for technical training in this operation. The application guides the user through a modular workflow, covering disassembly, cleaning, component replacement, and reassembly of the equipment. The simulator offers a safe and interactive environment for training critical skills, eliminating the risks of traditional methods and becoming a strategic, high-impact tool for the qualification of professionals in the power sector.